Wear Behavior Performance of Polymeric Matrix Composites Using Taguchi Experiments - Mohammed, Reem Alaa; Abdul Raheem, Ruaa Haitham; Khazaal, Shaymaa Hasan (Al-Khwarizmi Engineering Journal, 2019)
This research estimates the effect of independent factors like filler  (3%, 6%, 9%, 11% weight fraction), normal load (5N, 10N, 15N), and time sliding (5,7 , 9 minutes) on wear behavior of unsaturated polyester resin reinforced with jute fiber and waste eggshell and, rice husk powder composites by utilizing a statistical approach. The specimens polymeric composite prepared from resin unsaturated polyester filled with (4% weight fraction) jute fiber, and (3%, 6%, 9%, 11% weight fraction) eggshell, and rice husk by utilizing (hand lay-up) molding. Dry sliding wear experiments were carried utilizing a standard (pin on disc test setup) following a well designed empirical schedule that depends on Taguchi’s experimental design L9 (MINITAB 16) with the determined (S/N) ratio and analysis of different (ANOVA) optimal factors to minimize the wear rate. Results exhibit that the presence the of 11% weight fraction eggshell and rice husk powder with 4% weight fraction jute fiber improves the wear resistance of unsaturated polyester composite materials significantly. The filler content was observed to be the major significant factor influencing the wear rate followed by time sliding and normal load. From the results of the S/N ratio, the optimization of wear parameters is obtained at specimens A3, A6, A7, and A10 as to minimize wear rate.